Sly Moves : My Proven Program to Lose Weight, Build Strength, Gain will Power, and Live your Dream - Stallone, Sylvester and Hochman, David (New York Harper Collins, 2005)
The popular actor combines personal tales along with individualized workouts, tips on dieting, and advice for keeping fit and achieving lifelong goals.
Include Illustration, Indexes
Keywords: Physical fitness -- Weight loss -- Stallone, Sylvester